Method of Moment Analysis Using Open-Ended Coaxial Sensor in Determination of Corn Reflection Coefficient - Soleimani, Hojjatollah (2010)
The present thesis is a critical study on the use of an open-ended coaxial sensor for the estimation of moisture content of corn with various degrees of fruit ripeness at (25+1)oC. The fruit’s state of ripeness depends on moisture content. The permitivity is in direct relation with the amount of water in corn texture’ in other words, The higher the amount of water in the corn texture is, the higher the permittivity goes. An open-ended co-axial line has been used as an electromagnetic sensor or probe for various industrial and scientific applications. These applications are based on the principle that the characteristics of the echo signal produced by the co-axial opening depend upon the sample material terminating the probe. Thus, if the aperture admittance characteristics can be precisely formulated, then the electrical parameters of the sample can be found. The sensor was studied based on the calculation of reflection coefficient using an integral admittance approach and Method of Moment (MOM). The Method of Moment is one of the most important general methods which are used for solving electromagnetic-field problems. It begins with a brief mathematical foundation of the general method. Then, the various specializations are described, accompanied with relevant references to illustrate the pitfalls and shortcomings, as well as the advantages, as compared to other methods. So finally, their algorithms are easily programmable on computer. The computation of reflection coefficient of the corn was programmed using MATLAB software for the admittance approach and Method of Moment (MOM). The results were compared with the measured reflection coefficient using the open-ended coaxial sensor in conjunction with a vector network analyzer (VNA). The sensor operating between 1 GHz and 5 GHz was fabricated from a 2.05 mm and 0.65 mm, outer and inner diameters respectively. The measuring end of the sensor was calibrated by a transmission line procedure. The integral admittance formulation was simplified into a series expression. The local truncation errors of the series approximation were critically analyzed. The two-dimensional MOM was used to solve the rotationally symmetric region of the open-ended coaxial line. The MOM results are closed to the measurements data than calculated admittance formulation. The maximum absolute errors of MOM and measurement results for magnitude and phase reflection coefficient are less than 0.02 and 0.1 rad, respectively, compared with 0.05 and 0.2 rad of admittance formulation and measurement results, respectively. A calibration equation has been developed based on the relationship between the measured moisture content obtained by the oven drying method and the phase of the reflection coefficient of the sensor. The moisture content predicted by the sensor was in good agreement with those obtained using the standard oven drying method with its absolute error within 5 % moisture content, when tested on 114 different corn samples. The model successfully evaluated the complex permittivity for different ripeness stages of corn mesocarp as a function of frequency, moisture and ionic conductivity, as well as the bulk density. The software is also used to calculate reflection coefficient from complex permittivity in frequency between 1 GHz and 5 GHz.